Variability and Trend of Monthly Climatic Variables in Dinajpur District (Journal of Environmental Science and Natural Resources, 2012)
An attempt was made to investigate the monthly variability and trend for 20 climatic variables of Dinajpur district for 1948-2004. The variety of exploratory data analyses (EDA) tools and different robust and nonrobust measures were used for the analyses. The positive rates of total rainfall were fairly high in February, April, May, October and December where the residuals follow nonnormal and stationary but significant positive rate is documented only in September (+ 4.22*). The rate of growth of average cloud was documented less negative for August (- 0.0006) but significant positive for rest of the months. The rates of total frequency of insignificant rainfall were recognized approximately significant negative for April (- 0.035) and significant negative for May (- 0.069*) and September (- 0.079*), and the fairly high negative rates were accounted in February and December with nonnormal residual. Historical climatic data needs exploratory analysis and warrants tougher justification in classical analyses for outlier and residuals nonnormality and nonstationarity. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11559 J. Environ. Sci. & Natural Resources, 5(1): 89-98, 2012